Fenomena Manusia Silver sebagai Tindak Pidana Eksploitasi Ekonomi Anak: Analisis Pertanggungjawaban Pidana dan State Liability - Evangeline Ruth Berlianta G; Rocmad Dwi Riwayanto (Jurnal Hukum Lex Generalis, 2025)
The Silver Man phenomenon involving minors demonstrates the failure of child protection and law enforcement. This normative legal study analyzes this phenomenon as economic exploitation of children from the perspective of Indonesian Criminal Law. Based on the 1945 Constitution, Law No. 35 of 2014, and legal doctrine, the results show that the involvement of children fulfills the elements of the crime of economic exploitation of children, in accordance with Article 76I in conjunction with Article 88 of the Child Protection Law. Criminal liability is dual in nature. Parents must be subject to strict criminal sanctions on the basis of fault (dolus or culpa) for violating legal and moral obligations. The state also bears systemic non-criminal responsibility for negligence (omission of duty) in protection.